2002
DOI: 10.1212/wnl.59.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Distinctly abnormal brain metabolism in late-onset ornithine transcarbamylase deficiency

Abstract: These findings suggest progression of neurochemical events in OTCD, i.e., mI depletion and Gln accumulation followed by Cho depletion, which is reverse of that in hepatic encephalopathy, i.e., Cho depletion followed by mI depletion and Gln accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 21 publications
5
32
0
Order By: Relevance
“…The diminished concentration inversely correlated with the disease severity score, a measure of previous hyperammonemic episodes. Previous studies, by our group and others [13][14][15][16], shows that relative depletion of brain myoinositol as determined with 1 H MRS is a biomarker of OTCD, including asymptomatic carriers [16]. Here, we found that the concentration of brain myoinositol inversely correlated with clinical phenotype in three female members of a family with a known OTCD mutation that previously was associated with lethal, neonatal onset disease in a hemizygous male infant.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The diminished concentration inversely correlated with the disease severity score, a measure of previous hyperammonemic episodes. Previous studies, by our group and others [13][14][15][16], shows that relative depletion of brain myoinositol as determined with 1 H MRS is a biomarker of OTCD, including asymptomatic carriers [16]. Here, we found that the concentration of brain myoinositol inversely correlated with clinical phenotype in three female members of a family with a known OTCD mutation that previously was associated with lethal, neonatal onset disease in a hemizygous male infant.…”
Section: Discussionsupporting
confidence: 63%
“…This neurocognitive profile supports a nonverbal learning disability, characteristic of subcortical white matter dysfunction [12]. 1 H MRS studies have demonstrated elevations in glutamine and decreases in myoinositol and choline in patients who are clinically symptomatic [13][14][15].We recently used 1 HMRS to document a relative depletion of brain myoinositol in females who describe themselves as asymptomatic [16]. We have hypothesized that the decrement of myoinositol might constitute a useful biochemical marker with which to discriminate females with a partial deficiency.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations